Adapting a stand-alone computerized cognitive test battery for online use – A case-study in the context of users with special needs. (October 2016) - Hagelkruys, Dominik; Böhm, Christina; Motschnig, Renate; Kertzman, Semion; Sirota, Alexander; Lerer, Bernard; Gyarmathy, Éva
Abstract: As computers and internet access become more readily available at home, online testing and self-assessment are growing in popularity. In this article we briefly discuss the challenges and opportunities of online testing in general and then describe our experience with putting a standalone cognitive test battery online for users with special needs. Thereby the emphasis is on adopting the human-centered design process for the design of online tests and on the steps needed to be taken to arrive at a usable and validated online test battery. If the experience and process described in this paper turns out to be of value to researchers and/or practitioners in the field of using computers for human flourishing, this article will have achieved its purpose. Highlights: Adapting a stand-alone computerized cognitive test battery for online use Developing a suitable online testing environment for users with special needs Aiding users in handling their re-defined roles in the testing-process Exploiting interactive system to improve the user experience while performing cognitive tests